Valorising fish scale as sustainable gelatin source for emerging biomedical applications - Akash Nath Sharma; Piyas Bose; Saptarshi Mukherjee; Subhadeep Roy; Santanu Kaity (Bioresource Technology Reports, 2026)

Co-conditioning and parallel cell homing-driven pre-metastatic niche engineering: TGF-β-fuelled 3D microphysiological model for epithelial-mesenchymal transition in breast cancer - Madasu Vaishnavi; Mamta Kumari; Shreyashi Pal; Kulwinder Kaur; Santanu Kaity; Chandan Mandal; Subhadeep Roy (In vitro models, 2026)

Alleviating the Salinity Stress on Strawberry Using Plant Growth-Promoting Micro-organisms - G. M. Santhoshkumar; Nilesh Bhowmick; Ayon Roy; Abhas Kumar Sinha; Somnath Mandal; V. Sindhu; Kantamraju Prudveesh; Subhadeep Mandal; Souvik Ghosh (Applied Fruit Science, 2025)

Upcycling edible Musa balbisiana bracts waste into sustainable and possible 3D printable biomaterials - Shivam Rajput; Dipjyoti Sharma; Koushik Nandan Dutta; Subhadeep Roy; Subham Banerjee (Innovative Food Science & Emerging Technologies, 2025)

Isolated Bilateral Cerebellar Dysfunction as the Initial Manifestation of HIV Infection: A Diagnostic Challenge, Case Report, and Literature Review - Ritwick Mondal; Shramana Deb; Ananya Sengupta; Subhadeep Banerjee; Nirmalya Ray; Mona Tiwari; Jayanta Roy; Julián Benito-León (The Cerebellum, 2025)
Despite widespread access to antiretroviral therapy, neurological complications remain common in people living with human immunodeficiency virus (HIV). While opportunistic infections and HIV-associated malignancies are the usual causes, there is growing recognition of atypical, non-opportunistic neurological syndromes as early manifestations of HIV infection—even in the absence of prior diagnosis or treatment. We report the case of a 46-year-old woman with type 2 diabetes mellitus and a history of pulmonary tuberculosis who presented with a two-month history of progressive unsteady gait, dysarthria, and frequent falls. Neurological examination revealed isolated cerebellar dysfunction. Brain magnetic resonance imaging showed T2 and FLAIR hyperintensities in the bilateral middle cerebellar peduncles and adjacent white matter, suggestive of rhombencephalitis. Extensive diagnostic work-up for infectious, autoimmune, and paraneoplastic etiologies was negative. HIV testing revealed dual seropositivity for HIV-1 and HIV-2, with undetectable HIV-1 RNA and a low CD4 + T-cell count. The patient improved clinically with supportive care and was referred for antiretroviral therapy. At the two-month follow-up, she demonstrated marked recovery. Although cerebellar involvement in HIV is typically associated with opportunistic infections or neoplasia, this case illustrates that bilateral cerebellar dysfunction can represent the first clinical manifestation of HIV infection. We also review previously reported cases in which cerebellar signs were the initial presentation, emphasizing the need to consider HIV testing in patients with unexplained cerebellar syndromes.

Immiscible Two-Phase Flow in Porous Media: Effective Rheology in the Continuum Limit - Subhadeep Roy; Santanu Sinha; Alex Hansen (Transport in Porous Media, 2024)
We consider steady-state immiscible and incompressible two-phase flow in porous media. It is becoming increasingly clear that there is a flow regime where the volumetric flow rate depends on the pressure gradient as a power law with an exponent larger than one. This occurs when the capillary forces and viscous forces compete. At higher flow rates, where the viscous forces dominate, the volumetric flow rate depends linearly on the pressure gradient. This means that there is a crossover pressure gradient that separates these two flow regimes. At small enough pressure gradient, the capillary forces dominate. If one or both of the immiscible fluids percolate, the volumetric flow rate will then depend linearly on the pressure gradient as the interfaces will not move. If none of the fluids percolate, there will be a minimum pressure gradient threshold to mobilize the interfaces and thereby get the fluids moving. We now imagine a core sample of a given size. The question we pose is what happens to the crossover pressure gradient that separates the power-law regime from the high-flow rate linear regime and the threshold pressure gradient that blocks the flow at low pressure gradients when the size of the core sample is increased. Based on analytical calculations using the capillary bundle model and on numerical simulations using a dynamical pore-network model, we find that the crossover pressure gradient and the threshold pressure gradient decrease with two distinct power laws in the size. This means that the power-law regime disappears in the continuum limit where the pores are infinitely small compared to the sample size.

Environmental bisphenol A disrupts methylation of steroidogenic genes in the ovary of Paradise threadfin Polynemus paradiseus via abnormal DNA methylation: Implications for human exposure and health risk assessment - Sourav Kundu; Archisman Ray; Subhadeep Das Gupta; Ayan Biswas; Shreya Roy; Nitish Kumar Tiwari; V Santhana Kumar; Basanta Kumar Das (Chemosphere, 2024)

Diel variation of plankton in the highly impacted freshwater zone of Hooghly estuary in relation to ecological alteration - Trupti Rani Mohanty; Basanta Kumar Das; Nitish Kumar Tiwari; Suman Kumari; Kausik Mondal; Sourav Kundu; Subhadeep Das Gupta; Shreya Roy; Raju Baitha; Mitesh Hiradas Ramteke; Himanshu Shekhar Swain; Aurobinda Upadhyay (Environmental Monitoring and Assessment, 2024)

Bisphenol A contamination in Hilsa shad and assessment of potential health hazard: A pioneering investigation in the national river Ganga, India - Sourav Kundu; Ayan Biswas; Archisman Ray; Shreya Roy; Subhadeep Das Gupta; Mitesh Hiradas Ramteke; Vikas Kumar; Basanta Kumar Das (Journal of Hazardous Materials, 2024)

Stock Status of a Few Small Indigenous Fish Species Exploited in the River Ganga, India - Archisman Ray; Basanta Kumar Das; Dibakar Bhakta; Canciyal Johnson; Shreya Roy; Subhadeep Das Gupta; Soumya Prasad Panda; Raju Baitha (Fishes, 2023)
The River Ganga produces a substantial amount of its fish from small native species, defined here as those with a maximum length of 25 cm. The FiSAT program was utilized to estimate stock assessments of four important small indigenous species from the River Ganga: Johnius coitor, Cabdio morar, Salmostoma bacaila, and Gudusia chapra. Fish samples were collected monthly for a year (April 2020–May 2021) from four predetermined sampling sites along the River Ganga (Farakka, Berhampore, Balagarh, and Tribeni) in West Bengal, India. The estimated exploitation rate for Johnius coitor, Salmostoma bacaila, and Gudusia chapra was relatively lower than the optimum level of 0.5 and considerably lower than Emax values, indicating that their stocks are experiencing low fishing pressure in the region. The FiSAT results indicated that the species Cabdio morar was found to be heavily exploited. The total mortality (Z), natural mortality (M), and fishing mortality (F) rates for all four of the SIF species were examined, and they were contrasted with data from previous studies. On the lower stretch of the River Ganga, all of the fish stocks are optimally exploited (Eopt), except for the species Cabdio morar. The population dynamics of all of the species have been described for the first time on the lower stretch of the River Ganga. According to the findings, all of the fish stocks throughout the lower stretch of River Ganga are optimally exploited (Eopt), except for Cabdio morar. The study also emphasizes the importance of increasing sustainable fishing efforts, focusing on SIFs throughout the lower stretch of the River Ganga in order to safeguard the livelihood and nutritional status of fishermen.

Receptor model-based source apportionment and ecological risk assessment of metals in sediment of river Ganga, India - Basanta Kumar Das; Vikas Kumar; Lokenath Chakraborty; Himanshu Sekhar Swain; Mitesh Hiradas Ramteke; Ajoy Saha; Akash Das; Manisha Bhor; Aurobinda Upadhyay; Chayna Jana; Ranjan Kumar Manna; Srikanta Samanta; et al. (Marine Pollution Bulletin, 2023)

Hemato-biochemical alteration in the bronze featherback Notopterus notopterus (Pallas, 1769) as a biomonitoring tool to assess riverine pollution and ecology: a case study from the middle and lower stretch of river Ganga - Nitish Kumar Tiwari; Trupti Rani Mohanty; Subhadeep Das Gupta; Shreya Roy; Himanshu Sekhar Swain; Raju Baitha; Mitesh Hiradas Ramteke; Basanta Kumar Das (Environmental Science and Pollution Research, 2023)

A Preliminary Study of Butterfly Diversity in Hilly Terrains of Ghatsila, Jharkhand, India - Debarun Patra; Soumyajit Roy; Subhadeep Chowdhury; Asif Hossain; Pravat Kumar Shit; Surjyo Jyoti Biswas (Proceedings of the Zoological Society, 2022)

Turbulence effect on the mechanics of ripple formation under regular wave - Subhadeep Sarkar; Sayahnya Roy; Krishnendu Barman; Vikas K Das; Koustuv Debnath (Journal of Earth System Science, 2022)

Interaction among macrobenthic molluscan diversity of river Ganga and ecological variables by using multivariate indices - Shreya Roy; Canciyal Johnson; Nitish Kumar Tiwari; Subhadeep Das Gupta; Basanta Kumar Das (Arabian Journal of Geosciences, 2022)

The Co-Moving Velocity in Immiscible Two-Phase Flow in Porous Media - Subhadeep Roy; Håkon Pedersen; Santanu Sinha; Alex Hansen (Transport in Porous Media, 2022)
We present a continuum (i.e., an effective) description of immiscible two-phase flow in porous media characterized by two fields, the pressure and the saturation. Gradients in these two fields are the driving forces that move the immiscible fluids around. The fluids are characterized by two seepage velocity fields, one for each fluid. Following Hansen et al. (Transport in Porous Media, 125, 565 (2018)), we construct a two-way transformation between the velocity couple consisting of the seepage velocity of each fluid, to a velocity couple consisting of the average seepage velocity of both fluids and a new velocity parameter, the co-moving velocity. The co-moving velocity is related but not equal to velocity difference between the two immiscible fluids. The two-way mapping, the mass conservation equation and the constitutive equations for the average seepage velocity and the co-moving velocity form a closed set of equations that determine the flow. There is growing experimental, computational and theoretical evidence that constitutive equation for the average seepage velocity has the form of a power law in the pressure gradient over a wide range of capillary numbers. Through the transformation between the two velocity couples, this constitutive equation may be taken directly into account in the equations describing the flow of each fluid. This is, e.g., not possible using relative permeability theory. By reverse engineering relative permeability data from the literature, we construct the constitutive equation for the co-moving velocity. We also calculate the co-moving constitutive equation using a dynamic pore network model over a wide range of parameters, from where the flow is viscosity dominated to where the capillary and viscous forces compete. Both the relative permeability data from the literature and the dynamic pore network model give the same very simple functional form for the constitutive equation over the whole range of parameters.

Variation of Aulacoseira granulata as an eco-pollution indicator in subtropical large river Ganga in India: a multivariate analytical approach - Trupti Rani Mohanty; Nitish Kumar Tiwari; Suman Kumari; Archisman Ray; Ranjan Kumar Manna; Supriti Bayen; Shreya Roy; Subhadeep Das Gupta; Mitesh Hiradas Ramteke; Himanshu Sekhar Swain; Manisha Bhor; Basanta Kumar Das (Environmental Science and Pollution Research, 2022)

Rheology of Immiscible Two-phase Flow in Mixed Wet Porous Media: Dynamic Pore Network Model and Capillary Fiber Bundle Model Results - Hursanay Fyhn; Santanu Sinha; Subhadeep Roy; Alex Hansen (Transport in Porous Media, 2021)
Immiscible two-phase flow in porous media with mixed wet conditions was examined using a capillary fiber bundle model, which is analytically solvable, and a dynamic pore network model. The mixed wettability was implemented in the models by allowing each tube or link to have a different wetting angle chosen randomly from a given distribution. Both models showed that mixed wettability can have significant influence on the rheology in terms of the dependence of the global volumetric flow rate on the global pressure drop. In the capillary fiber bundle model, for small pressure drops when only a small fraction of the tubes were open, it was found that the volumetric flow rate depended on the excess pressure drop as a power law with an exponent equal to 3/2 or 2 depending on the minimum pressure drop necessary for flow. When all the tubes were open due to a high pressure drop, the volumetric flow rate depended linearly on the pressure drop, independent of the wettability. In the transition region in between where most of the tubes opened, the volumetric flow depended more sensitively on the wetting angle distribution function and was in general not a simple power law. The dynamic pore network model results also showed a linear dependence of the flow rate on the pressure drop when the pressure drop is large. However, out of this limit the dynamic pore network model demonstrated a more complicated behavior that depended on the mixed wettability condition and the saturation. In particular, the exponent relating volumetric flow rate to the excess pressure drop could take on values anywhere between 1.0 and 1.8. The values of the exponent were highest for saturations approaching 0.5, also, the exponent generally increased when the difference in wettability of the two fluids were larger and when this difference was present for a larger fraction of the porous network.

Identification and analysis of low light tolerant rice genotypes in field conditions and their SSR-based diversity in various abiotic stress tolerant lines - Sebantee Ganguly; Shoumik Saha; Sathish Vangaru; Shampa Purkayastha; Dibakar Das; Arup K. Saha; Anirban Roy; Subhadeep Das; Prabir K. Bhattacharyya; Subhra Mukherjee; Somnath Bhattacharyya (Journal of Genetics, 2020)

PHD-2 activation: a novel strategy to control HIF-1α and mitochondrial stress to modulate mammary gland pathophysiology in ER+ subtype - Uma Devi; Manjari Singh; Subhadeep Roy; Avinash C. Tripathi; Pushpraj S. Gupta; Shailendra K. Saraf; Md. Nazam Ansari; Abdulaziz S. Saeedan; Gaurav Kaithwas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Comparative efficacy of alpha-linolenic acid and gamma-linolenic acid to attenuate valproic acid-induced autism-like features - Sneha Yadav; Virendra Tiwari; Manjari Singh; Rajnish K. Yadav; Subhadeep Roy; Uma Devi; Swetlana Gautam; Jitendra Kumar Rawat; Mohd. Nazam Ansari; Abdulaziz Sa Saeedan; Anand Prakash; Shubhini A. Saraf; et al. (Journal of Physiology and Biochemistry, 2017)

α-Chymotrypsin regulates free fatty acids and UCHL-1 to ameliorate N-methyl nitrosourea induced mammary gland carcinoma in albino wistar rats - Asha Rani; Subhadeep Roy; Manjari Singh; Uma Devi; Rajnish K. Yadav; Swetlana Gautam; Jitendra K. Rawat; Mohd. Nazam Ansari; Abdulaziz S. Saeedan; Anand Prakash; Gaurav Kaithwas (Inflammopharmacology, 2016)

Redefining the role of peripheral LPS as a neuroinflammatory agent and evaluating the role of hydrogen sulphide through metformin intervention - Virendra Tiwari; Manjari Singh; Jitendra K. Rawat; Uma Devi; Rajnish K. Yadav; Subhadeep Roy; Swetlana Gautam; Shubhini A. Saraf; Vikas Kumar; Nazam Ansari; Abdulaziz S. Saeedan; Gaurav Kaithwas (Inflammopharmacology, 2016)